2019
DOI: 10.1039/c9py00183b
|View full text |Cite
|
Sign up to set email alerts
|

Alicyclic tertiary amine based hyperbranched polymers with excitation-independent emission: structure, fluorescence and applications

Abstract: Influence of the tertiary amine structure and its position in the hyperbranched macromolecules on the fluorescence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…[4][5][6] Hyperbranched and dendritic poly(amido amine) s are the first and most investigated unconventional polymers. [6][7][8][9] Since then, polymers containing electron-rich heteroatoms, such as poly(amino ester) (PAE), [6][7][8][9][10] hyperbranched polysiloxane, [11] polyacrylonitrile, [12] and polycarbonate, [13] have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] Hyperbranched and dendritic poly(amido amine) s are the first and most investigated unconventional polymers. [6][7][8][9] Since then, polymers containing electron-rich heteroatoms, such as poly(amino ester) (PAE), [6][7][8][9][10] hyperbranched polysiloxane, [11] polyacrylonitrile, [12] and polycarbonate, [13] have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Pan and Sun et al reported hyperbranched polymers containing only tertiary amines via thiol‐Michael addition polymerization of ethylene glycol diacrylate (EGDA) with tris(2‐mercaptoethyl)amine (TMEA) or N′,N′,N″‐tris(2‐mercaptoethyl) N‐aminoethyl piperazine(TMEAP), respectively. [ 39,40 ] They confirmed that the tertiary amine in branching point of hyperbranched polymers plays a key role in photoluminescence. Moreover, low cytotoxicity and bright cell imaging were observed from the galactose‐modified hyperbranched poly(amine ester)s. However, the preparation of thiol monomers TMEA or TMEAP need sophisticated multistep synthesis and purification, and the thiol monomers have offensive odor, toxicity, and limited storage stability, which are unpleasant and do not embrace the principles of green chemistry.…”
Section: Introductionmentioning
confidence: 91%
“…Subsequently, the effects of tertiary amine units and their position in linear and hyperbranched polymers on fluorescence properties, such as linear polymers with piperazine in the main and side chains, hyperbranched polymer with piperazine in the linear backbone and as branched units, as well as hyperbranched polymers with acyclic tertiary amines as the branched units were investigated. [48] As a result, a high fluorescence efficiency can be achieved by using tertiary amine as branching units due to its decreased mobility in hyperbranched polymers. Meanwhile, cell experiments also demonstrated their potential for fluorescence bioimaging.…”
Section: Self-fluorescent Polymers With Nitrogen-containing Chromophoresmentioning
confidence: 99%